Bioseparations Science and Engineering - Harrison, Roger G Todd, Paul (Oxford University Press, 1999)
The principal purpose of this book is to provide the most comprehensive and authoritative text on the science and engineering of bioseparations. The text is designed for students at all levels and is also intended to be useful for practitioners in industry.